Ethics in Higher Education: Using Collective Experiences to Enhance New Professional Training. Issue 4 (1st October 2016) - Holzweiss, Peggy; Walker, Daniel
Abstract : While ethical standards exist in higher education, they are often vague and do not identify the dilemmas new professionals are likely to encounter on the job. This article highlights results of a qualitative study identifying ethical dilemmas experienced by administrators in the field and compares results to the ethical framework developed by Janosik and associates (2004, 2007). A new dilemma type is identified and recommendations for further research and practice are made.